2015
DOI: 10.1080/00220388.2015.1068289
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Food Crop Marketing in Sub-Saharan Africa: Does Gender Matter?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Despites Ghana's economic development in recent times, poverty and food insecurity continuous to be high in the northern parts of the country than the southern parts [6]. This is not isolated to only Ghana since [7] reported that poverty is persistent among many small scale farmers in sub-Saharan Africa (SSA). The high dependence on agriculture by northern households predisposed them more to the negative consequences of climate change on food security.…”
Section: Introductionmentioning
confidence: 99%
“…Despites Ghana's economic development in recent times, poverty and food insecurity continuous to be high in the northern parts of the country than the southern parts [6]. This is not isolated to only Ghana since [7] reported that poverty is persistent among many small scale farmers in sub-Saharan Africa (SSA). The high dependence on agriculture by northern households predisposed them more to the negative consequences of climate change on food security.…”
Section: Introductionmentioning
confidence: 99%
“…Collective bargaining for example in farmer groups could reduce the number of middle men hence increase the farmers' share of the consumer price (Gruère et al, 2009). For instance, in Kenya female farmers who participate in groups, bulk their harvest and sell directly to the large trader, obtain higher prices for millet (Handschuch and Wollni, 2015). Moreover, lack of social capital and highlevel organization to strengthen internal and external relations with farmer groups and market chain actors equally influence individual marketing behaviour which in turn affect farmers' sales prices (Fafchamps and Minten, 2001;Kaganzi et al, 2009) Limited credit availability is another barrier to grain trade competition.…”
Section: Why Is There No Competition Between Traders Bidding Up Pricmentioning
confidence: 99%
“…There is some evidence (from Nairobi, Kenya) that the demand for finger millet among urban households increased significantly due to awareness of the nutritional value of finger millet and the importance of healthy eating [61,62]. This increase in demand has opened new marketing opportunities for finger millet in Kenya, resulting in higher prices of this traditional crop in Kenya than prices for maize or other cereals [62]. It is expected that these price incentives will motivate Kenyan farmers to expand their cultivation of finger millet.…”
Section: A Framework For Mainstreaming Nufcs For Sustainable Nutritiomentioning
confidence: 99%